Cultural Concept in Furniture Design: Perceptions, Issues and Challenges - Faridah Sahari; Musdi Shanat (ITB Journal Publisher, LPPM ITB, 2021)
Sarawak Borneo has long been known for its diverse culture and multi-ethnicity, which is reflected in its arts and crafts. Pua Kumbu and Orang Ulu are famous visual motifs that can be seen on many products from Sarawak, including textiles and paintings, which could potentially be integrated into furniture design as cultural elements. The purpose of this study was to identify the perception, issues and challenges of cultural concepts embedded in furniture design from the perspective of manufacturers, designers and the public. In-depth interviews, surveys and observation were the three qualitative research methods applied in this study at MIFF 2018 and MIFF 2019. In general, the findings from the surveys done in 2018 and 2019 show that manufacturers, designers and consumers agree that cultural elements can be a unique feature and a competitive advantage for furniture design. A range of furniture designs that feature different cultural elements, such as local materials, colors, stories and history, are discussed in this article, which is expected to inspire designers and manufacturers to experiment and explore this approach in furniture. However, to achieve this, manufacturers and designers have to have their own views and strategies on how they interpret cultural-related elements in furniture, based on their consumers’ interests and global market needs.